Brand logo design: examining consumer responses to figurativeness - Machado, J. C. (2017)
In a previous investigation, aimed at studying brand identity preferences in a merger context, researchers found the most preferred logos are figurative ones. Additionally, results suggested the aesthetic appeal of the logo significantly influences consumers’ identity choices. These results find support in logo strategy literature. The main purpose of this study is to investigate more thoroughly the influence of logo design characteristics, and particularly of figurativeness, on consumers’ responses. In two studies, this research will try to shed light on consumer logo preferences, by investigating psychological properties of figurativeness. Firstly, this research will allow classifying a significant sample of international logos according to the figurativeness of logo design. Then, this study will evaluate affect towards logo design.